Hidup dalam Ketidakpasatian: Ajakan Qohelet Untuk Takut Akan Tuhan - Epan, Yovianus; Saputro, Sigit Ani (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
This research focuses on exploring the book of Ecclesiastes from a Qohelet perspective. Using a qualitative method of literary-reflective text analysis, this study highlights Qohelet's personal experience in dealing with a world full of repetitive cycles and seemingly futile outcomes. In contrast to previous studies that emphasise psychological or pastoral approaches, this study offers novelty by exploring Qohelet's inner tension in contemplating the meaning of life. The results show that Qohelet feels limited in his search for meaning, but still invites readers to enjoy life as a gift from God despite its uncertainty.